21st Century Competencies in Light of the History of Integrated Curriculum - Drake, Susan M.; Reid, Joanne L. (Frontiers in Education, 2020)
Integrated or interdisciplinary curriculum is increasingly being recognized as a way to teach the 21st century competencies. Periods of implementation of integrated curriculum are reviewed to consider their relevance to the 21st century. To understand the history, the underpinnings of both traditional and progressive education are reviewed. As well, multiple definitions currently in use to describe integrated curriculum are identified on a continuum. Reasons to dismiss the continuum are also offered. Two periods when IC was implemented in a consistent way in United States are explored: the progressive era from 1919 to 1955, and the late 1980s and early 1990s. Similarities in each era are identified such as progressive principles about teaching and learning. Differences are also considered in basic assumptions held by curriculum developers of the day with the 1980s and 1990s lacking the 1930s deep social purpose of teaching for a democratic society. The socio-political context is visited to understand the beginnings and endings of these eras. The current educational context is then viewed from a global context. We see a landscape where, although there is deep concern for accountability and disciplines, there is also a global shift in what’s worth knowing to interdisciplinary competencies/skills/capabilities, well-being and teaching the whole child. Indeed, this happening in places across the planet such as Finland and New Zealand. The ideas are reminiscent of the 1930s progressive movement - a time of experimentation when integrated curriculum in a student-centered setting explored student interests instead of disciplinary knowledge. It is suggested that the unifying frameworks offered by different jurisdictions/nations in their curriculum documents and the ones developed by global education networks can act as a proxy for the Progressive Education Association that guided practitioners from 1919 to 1955.